2018
DOI: 10.1002/cbdv.201800161
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxonomic Considerations of the n‐Alkane Composition in Pinus heldreichii, P. nigra, and P. peuce

Abstract: The n-alkane composition in the leaf cuticular waxes of natural populations of Bosnian pine (Pinus heldreichii), Austrian pine (P. nigra), and Macedonian pine (P. peuce) was compared for the first time. The range of n-alkanes was wider in P. nigra (C - C ) than in P. heldreichii and P. peuce (C - C ). Species also diverged in abundance and range of dominant n-alkanes (P. heldreichii: C , C , and C ; P. nigra: C , C , C , and C ; P. peuce: C , C , C , and C ). Multivariate statistical analyses (PCA, DA, and CA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…As far as we know, this study is the very first report on diversity and differentiation of wax compounds within the genus Abies at the population level. Regarding n ‐alkane composition, Nikolić et al [32] . showed an overlap of 14 populations of three Pinus species ( P. heldreichii , P. nigra and P. peuce ) in several multivariate statistical analyses, which is in agreement with our findings.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…As far as we know, this study is the very first report on diversity and differentiation of wax compounds within the genus Abies at the population level. Regarding n ‐alkane composition, Nikolić et al [32] . showed an overlap of 14 populations of three Pinus species ( P. heldreichii , P. nigra and P. peuce ) in several multivariate statistical analyses, which is in agreement with our findings.…”
Section: Resultssupporting
confidence: 92%
“…As far as we know, this study is the very first report on diversity and differentiation of wax compounds within the genus Abies at the population level. Regarding n-alkane composition, Nikolić et al [32] showed an overlap of 14 populations of three Pinus species (P. heldreichii, P. nigra and P. peuce) in several multivariate statistical analyses, which is in agreement with our findings. Once again, another type of phytochemical markers (terpenes) showed good grouping of populations within these Pinus species, positioning them in accordance with infrageneric classification.…”
Section: Population Differentiationsupporting
confidence: 93%
See 2 more Smart Citations
“…Pine trees are evergreen conifers belonging to the genus Pinus of the family Pinaceae . The genus Pinus exhibits a taxonomical variety of about 115 species and occurs mainly in the northern hemisphere [ 1 , 2 , 3 , 4 ]. Needles and twigs are source of pine essential oils (EOs), used to treat respiratory infections based on their antibacterial, anti-inflammatory, expectorant and analgesic potential [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%